Determinant Factors of Depression in Beta Major Thalassemia Children - Suryawan, Ahmad; Ningtiar, Hapsari Widya; Irwanto, Irwanto; Ugrasena, I Dewa Gede (Folia Medica Indonesiana, 2021)
Thalassemia is a chronic disease with long-term treatment that increases the potential for impact on physical, cognitive, and psychological conditions. About 80% of patients with major thalassemia have at least one psychiatric disorder, depression is one of the most frequently reported, especially in prepubertal and puberty periods. The aim of this study is to evaluate determinant factors of depression in beta mayor thalassemia children. This was a cross-sectional study on patients aged 9 to 17 years at hematology outpatient clinic in Dr. Soetomo General Hospital from September to Desember 2018. Level of depression determinded by Children Depression Inventory (CDI) questionnaire. The data were collected and analyzed using using the IBM SPSS Statistics version 21. It is statistically significant with p<0.05. Forty-five participants were included in this study, 15 participants with mild depression and 30 participants without depression. Gender (p=0.462), age of diagnosis (p=0.385), frequency of tranfussion (p=0.065), family history of depression (p=0,350), physical change (p=0.711), duration of illness (p=0.674) have no significant value as a determinant factor while complication (p=0.049) and serum cortisol level (p=0.037) had significant value as determinant factors of depression in Beta Major Thalassemia children. Mild depression is more common in thalassemia patients who experience complications and had high serum cortisol levels